Mosaic of memories : varied experiences of a member of the civil service - Shamsul Haque, A. T. M., 1937- (Dhaka, Bangladesh : Pathak Shamabesh, 2007)
Memoirs of the author, a civil servant from Bangladesh.
Includes index.
Keywords: Shamsul Haque, A. T. M., -- 1937-; Civil service -- Bangladesh -- Biography; Bangladesh -- Officials and employees -- Biography